Economic Viability and Legal Aspect of Fiscal Federalism in Nepal - Dhakal, Chandra Prasad (Journal of Development Review, 2023)
Fiscal federalism is one of the important tools for economic viability in the nation. Nepal follows federal system of government with allocation of certain economic rights to federal units. Constitution of Nepal (2015) makes the provision of three levels of government and all the governments have certain financial rights such as preparing and implementing the budget in its' territory. The study analyzes economic viability and legal aspect of fiscal federalism in Nepal. Objectives of the study are to highlight the legal aspects of financial federalism and analyze budget practice of fiscal federalism of Nepal. Qualitative research design was used to fulfill the objectives of the study. Only secondary source of data was used for this study. Data were collected through library research and interpretive paradigm was used to complete the research. Finding and conclusion of the study has been based on interpretation of data. The implementation fiscal federalism is not effective in Nepal as well as implementation mechanism of the governments is found also weak that makes fiscal federalism as controversial issue in economic development.